Answer:
b=-3
Step-by-step explanation:
If the expression simplifies to bx that means the [tex]x^{2}[/tex] terms and the constant terms must be cancel out.
Simplify it first.
[tex](4x+4)(ax-1)-x^{2} +4\\=(4ax^{2} -4x+4ax-4)-x^{2} +4\\=4ax^{2} -x^{2} -4x+4ax-4+4\\=4ax^{2} -x^{2} -4x+4ax[/tex]
We know –4 + 4 will cancel out. If we simplify this expression to only an x term, then the [tex]x^{2}[/tex] terms should be cancelled. Therefore, we say that 4ax^2 – x^2 = 0.
[tex]4ax^{2} -x^{2} =0\\x^{2} (4a-1)=0\\4a-1=0\\4a=1\\a=\frac{1}{4}[/tex]
If we put a = ¼, then we can find the value of b:
[tex]=4(\frac{1}{4} )x^{2} -x^{2} -4x+4(\frac{1}{4} )x\\=x^{2} -x^{2} -4x+x\\ (cancel out x^{2} terms)\\[/tex]
[tex]=-3x[/tex]
[tex]bx=-3x\\[/tex] if the expression is equivalent to bx
Therefore, b = –3.